THE EFFECT OF VITAMIN E (α-TOCOPHEROL) TO TNF-α SERUM LEVELS IN WISTAR WHITE STRAIN RATS EXPOSED TO CISPLATIN - Muhammad Shidqy, Eldien; M. Soebadi, Doddy; Hakim, Lukman (Indonesian Urological Association, 2020)
Objective: To analyze the protective effect of vitamin E on TNF-α levels in white Wistar strains exposed to Cisplatin. Material & Methods: The design of this study was an experimental laboratory with post-test only control group design, with the evaluation of TNF-α levels carried out after the animals were treated. The grouping of experimental animals was carried out by randomization. This study using male Wistar white rats as samples. The control group in this study included a negative control group (CN), which was given an injection of 1 cc intravenous normal saline 0.9% on the 7th day as a placebo, then on the 10th day the blood sample was taken. The positive control group (CP), which was given cisplatin treatment at a dose of 5 mg/kg intraperitoneally, once on the 7th day. Treatment group (P1) was treated using cisplatin 5 mg/kg intra-peritoneally and Vitamine E 100 mg/KgBW, and Treatment group (P2) was treated using cisplatin 5 mg/kg intra-peritoneally and Vitamine E 200 mg/KgBW. Blood samples were taken on the 10th day, intra-cardiac and TNF-α levels were analyzed using ELISA. Results: There were significant differences in the mean TNF-α levels in the negative control group for all treatment groups with a p-value <0.05. There was also a significant difference in TNF-α levels in the positive control group for treatment group 1 and treatment 2 with p<0.05. On the other hand, further analysis showed that there was no significant difference between treatment group 1 and treatment group 2 (p>0.05). Conclusion: TNF-α levels in mice given cisplatin was much higher compared with the control group. Vitamin E 100 and 200 mg/kgBW cause a decrease in TNF-α protein levels in mice injected with cisplatin when compared with controls. There is no difference in TNF-α levels in mice receiving vitamin E at doses of 100 and 200 mg/kgBW